Pelatihan Menulis Teks Bahasa Inggris Melalui Pendekatan Saintifik Terintegrasi Dengan Teknik Mind Mapping Bagi Siswa SMK Plus Insan Andalan Cianjur - Nurviyani, Vina; Helmie, Jauhar; Ningsih, D. Nurfajrin; Utama, Gina Nanda; Burki, Audrey Bianca; Halimatu Sya’diah, Siti Nurhayati (Universitas Pahlawan Tuanku Tambusai, 2025)
In the globalization era, students should have the ability to communicate in English. However, the results of the need analysis conducted at SMK Plus Insan Andalan Cianjur showed that students needed to improve their English skills, especially writing skills. One of the solutions is writing coaching of English texts through the scientific approach integrated with mind mapping technique. The purpose of the writing coaching is to improve students' literacy competency, particularly students' English writing skills. The writing coaching was carried out face-to-face involving 40 students in grade 10. The writing coaching was carried out in three stages, i.e., preparation of writing coaching, implementation of writing coaching, and evaluation of writing coaching. Referring to the results of observations, interviews, and questionnaires, the findings show that the implementation of a scientific approach integrated with mind mapping techniques facilitate students to get ideas and compose English sentences more easily so that students are more enthusiastic in writing English texts. Thus, the students’ literacy competencies can be improved more optimally.